COMET Muon Conversion Experiment in J-PARC - Lee, MyeongJae (Frontiers in Physics, 2018)
COMET is an experiment at J-PARC, Japan, which will search for neutrinoless conversion of muons into electrons in the field of a nucleus (μ− + N → e− + N); a lepton flavor violating process. The experimental sensitivity goal for this process is order of 10−15 for Phase-I and 10−17 for Phase-II experiment, which is a factor of 100–10,000 improvements correspondingly over existing limits. Recent progresses in facility and detector development are presented, along with COMET Phase-I and Phase-II experimental schedule.